Contributing factors for self-reported HIV in male Peruvian inmates: results of the 2016 prison census - Culquichicón, Carlos; Zapata-Castro, Luis E.; Soto-Becerra, Percy; Silva-Santisteban, Alfonso; Konda, Kelika A.; Lescano, Andrés G. (Frontiers in Public Health, 2023)
Introduction: Worldwide, prisons are high-risk settings for the transmission of infectious diseases such as HIV. There is a need to understand the health conditions of prisoners to improve and implement timely strategies for HIV diagnosis and control. Hence, we aimed to identify factors associated with self-reported HIV (srHIV) among Peruvian inmates.This study is a secondary data analysis of the First Peruvian Prison Census conducted in 2016. We estimated the prevalence of srHIV in prisoners who were male at birth and the association of srHIV with other social conditions, criminal records, and prevalent health conditions. Nested models identified a multivariable parsimonious model for factors associated with srHIV and yielding prevalence ratios adjusted by the included parameters.The census surveyed 71,087 male inmates of whom 0.4% reported srHIV (n=305), and 82% of whom were receiving antiretroviral treatment (n=220). In our final multivariable model, srHIV was independently associated with age between 36-55 years old vs. >55 years old [parsimonious prevalence ratio (pPR)=1.98, 95% CI, 0.96-4.08], having a stable partner out of prison [pPR=1.64, 95% CI, 1.24-2.19], being homosexual [pPR=4.16, 95% CI, 2.50-6.90], self-report of prevalent tuberculosis coinfection [pPR=2.55, 95% CI, 1.82-3.58], self-report of prevalent sexually transmitted infections [pPR= 34.49, 95% CI,, and self-report of prevalent illicit drug use 30 days before the survey [pPR=1.91, 95% CI, 1.43-2.56].Self-reported HIV is associated with multiple social, health and prison risks among Peruvian inmates. Deeply understanding these factors would help to design HIV prevention and control strategies in Peruvian prisons.